Sexual behaviour change following HIV testing services: a systematic review and meta‐analysis. Issue 11 (8th November 2020) - Tiwari, Ruchi; Wang, Jiayu; Han, Hannah; Kalu, Ngozi; Sims, Lee B; Katz, David A; Burke, Barbara; Tsegaye, Adino T; Carter, Kayla A; Freije, Sophie; Guo, Boya; Albirair, Mohamed; et al.
Abstract: Introduction: Learning one's HIV status through HIV testing services (HTS) is an essential step toward accessing treatment and linking to preventive services for those at high HIV risk. HTS may impact subsequent sexual behaviour, but the degree to which this varies by population or is true in the setting of contemporary HIV prevention activities is largely unknown. As part of the 2019 World Health Organization Consolidated Guidelines on HTS, we undertook a systematic review and meta‐analysis to determine the effect of HTS on sexual behaviour. Methods: We searched nine electronic databases for studies published between July 2010 and December 2019. We included studies that reported on at least one outcome (condom use [defined as the frequency of condom use or condom‐protected sex], number of sex partners, HIV incidence, STI incidence/prevalence). We included studies that prospectively assessed outcomes and that fit into one of three categories: (1) those evaluating more versus less‐intensive HTS, (2) those of populations receiving HTS versus not and (3) those evaluating outcomes after versus before HTS. We conducted meta‐analyses using random‐effects models. Results and discussion: Of 29 980 studies screened, 76 studies were included. Thirty‐eight studies were randomized controlled trials, 36 were cohort studies, one was quasi‐experimental and one was a serial cross‐sectional study. There was no significant difference in condom use among individuals receiving more‐intensive HTS compared to less‐intensive HTS (relative risk [RR]=1.03; 95% CI: 0.99 to 1.07). Condom use was significantly higher after receiving HTS compared to before HTS for individuals newly diagnosed with HIV (RR = 1.65; 95% CI: 1.36 to 1.99) and marginally significantly higher for individuals receiving an HIV‐negative diagnosis (RR = 1.63; 95% CI: 1.01 to 2.62). Individuals receiving more‐intensive HTS reported fewer sex partners at follow‐up than those receiving less‐intensive HTS, but the finding was not statistically significant (mean difference = −0.28; 95% CI: −3.66, 3.10). Conclusions: Our findings highlight the importance of using limited resources towards HTS strategies that focus on early HIV diagnosis, treatment and prevention services rather than resources dedicated to supplementing or enhancing HTS with additional counselling or other interventions.